2020
DOI: 10.1177/0954406220943221
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic compression and tensile responses of an epoxy matrix composites at high strain rate

Abstract: To study the dynamic compression and tensile mechanical behaviors of a bicomponent epoxy resin matrix composites, which were filled with a semi-crystalline thermoplastic Polyether-ether ketone (PAEK-C) resin, at high strain rate, the dynamic compression and tensile experiments were carried out on a modified split Hopkinson pressure bar (SHPB) and high speed material apparatus, respectively. Stress-strain curves of the epoxy resin matrix composites were obtained and analyzed. Damage mechanism under high strain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…Previous studies have shown that the mechanical properties of the thermosetting resins were significantly improved without reducing the heat resistance by incorporating PAEK resin. 20,21…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that the mechanical properties of the thermosetting resins were significantly improved without reducing the heat resistance by incorporating PAEK resin. 20,21…”
Section: Introductionmentioning
confidence: 99%
“…Polyaryletherketone (PAEK) is a family of the highperformance engineering thermoplastics notable for their excellent mechanical properties, high temperature performance and thermal stability. [17][18][19] It has been extensively used in aerospace, electronics, automobile manufacturing, and other particularly demanding industries. Also, it has been widely applied in modifying polymer composites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous work indicated that the PAEK-C could enhance the dynamic impact mechanical and the nanomechanical properties of the epoxy resin matrix composites significantly. 34,35…”
Section: Introductionmentioning
confidence: 99%
“…7 Epoxies, also known as thermosetting eco-friendly polymers, are extensively used as a matrix material in the manufacturing of sophisticated high-performance materials due to their dimensional stability, chemical stability, ease of processing, low shrinkage, excellent mechanical, thermal, and physical characteristics. [8][9][10][11][12] The properties viz. elastic modulus, 13,14 tensile strength, 14 flexural strength, 15,16 impact strength, 15,16 friction coefficient, 13 wear resistance, 13 thermal stability, 13,14,17 and flame retardancy 17,18 of epoxy is improved with the addition of nano-filler materials.…”
Section: Introductionmentioning
confidence: 99%